2016
DOI: 10.2459/jcm.0000000000000300
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent pericarditis in children and adolescents

Abstract: Recurrent pericarditis has an overall favourable prognosis in children, although it may require frequent readmissions and seriously affect the quality of life, especially in patients treated with corticosteroids. Colchicine or anakinra therapies were associated with significant decrease in the risk of recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
64
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 106 publications
(117 reference statements)
1
64
0
6
Order By: Relevance
“…However, a 2016 systematic review demonstrated a lack of evidence to support or discourage the use of colchicine in pediatric pericarditis (Alabed, P erez-Gaxiola, & Burls, 2016). Furthermore, a multicenter cohort study done by Imazio et al (2016) demonstrated a significant decrease in the risk of recurrence of pericarditis, whereas the use of corticosteroids in adults has been associated with an increased risk of recurrence (Seferovi c et al, 2013). Recurrence of pericarditis in children ranges from 15% to 40% (Shakti et al, 2014).…”
Section: Treatment Planmentioning
confidence: 99%
“…However, a 2016 systematic review demonstrated a lack of evidence to support or discourage the use of colchicine in pediatric pericarditis (Alabed, P erez-Gaxiola, & Burls, 2016). Furthermore, a multicenter cohort study done by Imazio et al (2016) demonstrated a significant decrease in the risk of recurrence of pericarditis, whereas the use of corticosteroids in adults has been associated with an increased risk of recurrence (Seferovi c et al, 2013). Recurrence of pericarditis in children ranges from 15% to 40% (Shakti et al, 2014).…”
Section: Treatment Planmentioning
confidence: 99%
“…Помимо вышеперечисленных изменений, в исследованиях M. Raatikka, A. Brucato, и M. Imazio описаны также такие симптомы и синдромы, как выпот в полость плевры у 36-56% пациентов и повышение аминотрансфераз в 8% случаев [33,34]. По данным нашего исследования у 20 пациентов с ИРП выпот в полость плевры выявлен в 80% случаев, а повышение аминотрансфераз в 50%, что не укладывается в представление о классическом течении перикардита (табл.…”
Section: клиническая картинаunclassified
“…Similar to adults, a number of children with IRP have been treated successfully with anakinra (6, 31, 32). The anakinra dose was 100 mg/day for adults (30, 33, 34) and 1–2 mg/kg/day (up to 100 mg/day) for children (3, 31, 33).…”
Section: Current Therapeutic Algorithm For the Treatment Of Recurrentmentioning
confidence: 99%